The Dynamic Interpretation of Pancasila in Indonesian State Administration History: Finding Its Authentic Interpretation - Wendra Yunaldi (Jurnal Hukum Novelty, 2020)
Introduction to The Problem: The term interpretation of Pancasila seems rarely used to measure the substance of the Pancasila as the Indonesian nation’s weltanschauung. The term interpretation refers to the concept of constitutional and cultural meaning so that the order of civic life is in the same direction and under the paradigm of God, humanity, unity, society, and social justice. After the amendment of the 1945 Constitution, the Indonesian constitution has faced many changes. The changes that occurred are to creating a democratic governmental order. Even though the democratic rule of the government has surfaced, one thing for sure is that Pancasila is strengthening the form of Indonesia’s foundation. Because philosophy, enthusiasm, ideas, and thoughts of the nation’s life are determined by the underlying weltanschauung.Purpose/Objective Study: This study is trying to find the authentic interpretation of Pancasila based on its dynamic interpretation throughout Indonesian history.Design/Methodology/Approach: To answer these problems, the method used in this study is normative research with a conceptual approach so that interpretation is obtained by the paradigm built by the nation’s founders.Findings: By referring to library materials, the conclusion that can be drawn from this research is Pancasila, which is misinterpreted rigidly and is state-oriented to castrate the meaning of Pancasila as a public view of life. Then with the strong tendency of legal-formal interpretation so that it eliminates its substantive nature as weltanschauung or national outlook on life so that Pancasila loses its vital in the present state of life in Indonesia.